Changing perceptions of protected area benefits and problems around Kibale National Park, Uganda. (15th September 2017) - MacKenzie, Catrina A.; Salerno, Jonathan; Hartter, Joel; Chapman, Colin A.; Reyna, Rafael; Tumusiime, David Mwesigye; Drake, Michael
Abstract: Local residents' changing perceptions of benefits and problems from living next to a protected area in western Uganda are assessed by comparing household survey data from 2006, 2009, and 2012. Findings are contextualized and supported by long-term data sources for tourism, protected area-based employment, tourism revenue sharing, resource access agreements, and problem animal abundance. We found decreasing perceived benefit and increasing perceived problems associated with the protected area over time, with both trends dominated by increased human-wildlife conflict due to recovering elephant numbers. Proportions of households claiming benefit from specific conservation strategies were increasing, but not enough to offset crop raiding. Ecosystem services mitigated perceptions of problems. As human and animal populations rise, wildlife authorities in Sub-Saharan Africa will be challenged to balance perceptions and adapt policies to ensure the continued existence of protected areas. Understanding the dynamic nature of local people's perceptions provides a tool to adapt protected area management plans, prioritize conservation resources, and engage local communities to support protected areas. Highlights: Percentage of households claiming benefit decreased over time. Percentage claiming problems increased over time with elephant abundance. Benefit influenced by employment, tourism, revenue sharing and resource access. Improving benefits overshadowed by crop raiding problems. Wildlife conflict dominated but problem mitigated by ecosystem service benefit.